Effect of Adding Biomin as a Natural Growth Promoter on Productive Performance, Some Haematological and Immunological Traits of Broiler Chicks - EL-Kaiaty , A.M.; Mohamed, F.R.; Abdel-Kareem, A.A.A.; Eita, E.M. Abou; Eshra, A.A.M. (International Journal of Poultry Science, 2015)
The objective of the present study was to investigate the effect of adding Biomin as a natural growth promoter in drinking water on the productive performance, some hematological and immunological parameters in broiler chicks. A total of 180 unsexed, one day old, broiler chicks (Hubbard) were weighed, wing banded and randomly classified to three equal groups. All chicks in the 1st group were watered fresh tap water during the experiment, while those in the 2nd and 3rd groups were orally received fresh tap water including 20 and 30 mg Biomin/chick during the first three days of age. All chicks were fed on commercial basal diets ad libitum and daily exposed to 24 lighting hours allover experimental period. All birds were reared on a partitioned deep litter floor. The obtained results could be concluded as follow: The oral administration of Biomin to broiler chicks increased (p